Piano Sonata no. 18 in E-flat major, op. 31, no. 3, arranged for string quartet - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Ries, Ferdinand, 1784-1838 (arranger):::Contributor:::::::::::: (Germany; Frankfurt am Main; Fr. Ph. Dunst, 2025)
Early edition of the Piano sonata no. 18 in E-flat major, op. 31, no.3, arranged for string quartet by Ferdinand Ries.